Say , I have two equations :

$$y_1=a+bx_{1}+e_1$$ $$y_2=a+bx_{2}+e_2$$

Say , $a=.5$ , $b=2.1$ , $x_1=2$ , $x_2=2.2$ .

Now if $e_1=e_2$ , I have to find the relationship between $y_1$ and $y_2$ .

So i started as :

$$e_1=e_2$$ $$\Rightarrow y_1-(a+bx_{1})=y_2-(a+bx_{2})$$ $$\Rightarrow y_1-[.5+(2.1)(2)]=y_2-[.5+(2.1)(2.2)]$$ $$\Rightarrow y_1-4.7=y_2-5.12$$ $$\Rightarrow y_1=y_2-5.12+4.7$$ $$\Rightarrow y_1=y_2-.42$$ But when i started to cross-check , that is ,

Holding $a=.5$ and $b=2.1$ and $x_{1}=2$ , $x_{2}=2.2$ and the relationship $y_1=y_2-.42$ , when $y_1=5$ , $y_2=4.58$ , then




That is , $$e_1\ne e_2\quad\text{!!! }$$

But for this example I established the relationship if $$e_1=e_2\quad\text{then}\quad y_1=y_2-.42$$ . Then why is the converse not true , i.e., if $$y_1=y_2-.42\quad\text{then}\quad e_1=e_2$$



If $y_1 = y_2 - 0.42$, then if $y_1= 5$, the value of $y_2$ should not be $4.58$, because $5\neq 4.58-0.42!$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.